Plants : flowering plants, ferns, mosses, and other plants - Levine, Shar, 1953- (Class of their own., 2010)
The plant kingdom contains more than 250,000 species. With green pigment called chlorophyll in some cells, these organisms have the unique ability to make their own food. This colorful book describes the main groups of plants, including mosses, ferns, conifers, and flowering plants. Special sections highlight the role of plants in the environment--as producers in the food chain and producers of the world's oxygen--and their role in climate and the water cycle. Case histories include the discovery of a new species of conifer tree in Australia and special cases of plant breeding.